Purchase of ultra-processed foods in Norway: a repeated cross-sectional analysis of food sales in 2013 and 2019 - Marie Michaelsen Bjøntegaard; Marianne Molin; Marit Kolby; Liv Elin Torheim (Cambridge University Press, 2023)
Abstract Objective: A dietary pattern dominated by ultra-processed foods has been associated with non-communicable diseases in several studies. A previous study from 2013 found a high share of ultra-processed foods in Norwegian food sales. This study aimed to investigate the current share of ultra-processed foods in Norway and the development in expenditure on ultra-processed foods from 2013. Design: A repeated cross-sectional analysis of scanner data from the Consumer Price Index from September 2013 and 2019 and an investigation of the processing degree according to the NOVA classification system. Setting: Food sales in Norway. Participants: Norwegian grocery stores (n 180, for both time periods). Results: The share of expenditure in 2019 was highest for ultra-processed foods (46·5 %) and minimally or unprocessed foods (36·3 %), followed by processed foods (8·5 %) and processed culinary ingredients (1·3 %). An increasing degree of processing was found for several of the food groups between 2013 and 2019; however, most effect sizes were weak. In 2019, soft drinks became the most frequently purchased food item, surpassing milk and cheese, with the highest expenditure in Norwegian grocery stores. Increases in expenditure on ultra-processed foods were mainly due to increased expenditures on soft drinks, sweets and potato products. Conclusions: A high share of expenditure on ultra-processed food was found in Norway, which may imply a high consumption of these foods. The change in expenditure of NOVA groups between 2013 and 2019 was small. Carbonated and non-carbonated soft drinks were the most frequently purchased products in Norwegian grocery stores and contributed to most of the expenditures.